2020
DOI: 10.1111/1749-4877.12422
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic status of Chinese blue sheep (Pseudois nayaur): new evidence of a distinct subspecies

Abstract: The blue sheep is an endemic species to the Qinghai-Tibet Plateau and surrounding regions. It has been regarded as having 2 subspecies: Pseudois nayaur nayaur and P. n. szechuanensis. However, such a classification remains controversial. Herein, we analyze 10 microsatellite loci and part of the mitochondrial control region for clarification in such taxonomic debates. We use samples from 168 individuals from 6 geographic populations covering almost all the distribution areas of the species in China to carry out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The bharal, also known as blue sheep ( Pseudois nayaur ), is a mountain ungulate endemic to the Pan-Himalaya area [ 12 ]. Most of the blue sheep populations in the Trans-Himalayas region live on high elevation mountain scree, avoiding habitat below 4000 m [ 13 ], while populations in the Yangze Gorge, southwest China, once considered as a full species, were also found below the forest belt [ 14 ]. A long-standing controversy exists about the taxonomical status of the low elevation populations, once named dwarf blue sheep ( Pseudois schaeferi ) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bharal, also known as blue sheep ( Pseudois nayaur ), is a mountain ungulate endemic to the Pan-Himalaya area [ 12 ]. Most of the blue sheep populations in the Trans-Himalayas region live on high elevation mountain scree, avoiding habitat below 4000 m [ 13 ], while populations in the Yangze Gorge, southwest China, once considered as a full species, were also found below the forest belt [ 14 ]. A long-standing controversy exists about the taxonomical status of the low elevation populations, once named dwarf blue sheep ( Pseudois schaeferi ) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the blue sheep populations in the Trans-Himalayas region live on high elevation mountain scree, avoiding habitat below 4000 m [ 13 ], while populations in the Yangze Gorge, southwest China, once considered as a full species, were also found below the forest belt [ 14 ]. A long-standing controversy exists about the taxonomical status of the low elevation populations, once named dwarf blue sheep ( Pseudois schaeferi ) [ 14 , 15 ]. Mitochondrial DNA and microsatellite markers were used to clarify the evolutional relationship of a geographically isolated population, but controversial conclusions on the taxa were proposed [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the factors contributing to the limited gene flow between LA and LS area is likely to be limited physical corridor and patchiness in suitable area. The previous studies also suggested influence of geographic distance and landscape barrier on the genetic distance in blue sheep population 33 . Likewise, we also obtained a significant IBD and sPCA results suggested that individuals sampled on the periphery have higher genetic divergence than the central populations (Figs.…”
Section: Discussionmentioning
confidence: 86%
“…To date, most landscape genetic studies of the IBD have focused on the genetic diversity and differentiation across geographic populations using genetic markers, typically microsatellites (James 1983;Merilä 1997;Andersen et al 2004;Jehle et al 2005;Hu et al 2011;Gao et al 2020). As such, these studies have been restricted to a few genetic loci.…”
Section: Introductionmentioning
confidence: 99%